2020
DOI: 10.1002/pros.24076
|View full text |Cite
|
Sign up to set email alerts
|

A phase II randomized placebo‐controlled trial of pomegranate fruit extract in men with localized prostate cancer undergoing active surveillance

Abstract: Introduction or Objective: Men with favorable-risk prostate cancer (PCa) on active surveillance may benefit from intervention strategies to slow or prevent disease progression and the need for definitive treatment. Pomegranate and its extracts have shown antiproliferative and proapoptotic effects in cell lines and animal models, but its effect on human prostate cancer as a target tissue remain unclear. Objectives of this trial include pomegranate's ability to alter serum and prostate tissue biomarkers and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
0
6
0
3
Order By: Relevance
“…After 52 weeks of PPE intaking in humans with high-risk prostate cancer, 8-hydroxy-2′-deoxyguanosine (8-OHdG) was reduced in tumor tissue, androgen receptor expression was downregulated in adjacent tissues, and urolithin was also detected in prostate tissue. However, there were no significant effects on insulin-like growth factor-1 (IGF-1), insulin-like growth factor-binding protein 3 (IGFBP-3), free testosterone levels, PSA doubling times, and biopsy indices compared with the placebo group ( 68 ).…”
Section: Physiological Functionsmentioning
confidence: 99%
“…After 52 weeks of PPE intaking in humans with high-risk prostate cancer, 8-hydroxy-2′-deoxyguanosine (8-OHdG) was reduced in tumor tissue, androgen receptor expression was downregulated in adjacent tissues, and urolithin was also detected in prostate tissue. However, there were no significant effects on insulin-like growth factor-1 (IGF-1), insulin-like growth factor-binding protein 3 (IGFBP-3), free testosterone levels, PSA doubling times, and biopsy indices compared with the placebo group ( 68 ).…”
Section: Physiological Functionsmentioning
confidence: 99%
“…However, the hypothesis of the protective effect of pomegranate extract against oxidative damage was supported by the capability of its metabolite -Urolithin A of absorption and accumulation in prostate tissues, while high Urolithin A levels correlated with lower 8OHdG levels [94]. Nevertheless, the results from a recent study by Jarrard et al (2021) concluded that pomegranate compounds could affect biomarkers of oxidative stress demonstrated by reduced 8OHdG and androgen receptor expression in prostate tumour associated with pomegranate fruit extract in men with organ-confined, favourable-risk PCa [95]. In comparison with pomegranate impact discussed above in men with rising PSA following initial PCa therapy [93], daily pomegranate demonstrated no effect on PSA levels in recurrent and advanced PCa patients compared with placebo [96].…”
Section: Pomegranate Polyphenolsmentioning
confidence: 99%
“…La expresión de 8-hidroxi 2'-desoxiguanosina en el cáncer Tequio 5 (15), 2022: [31][32][33][34][35][36][37][38][39][40] ISSN: 2594-0546 TEQUIO, mayo-agosto 2022, vol. 5, no.…”
Section: -Hydroxy 2'-deoxyguanosine Expression In Cancerunclassified
“…Los tejidos del grupo que consumió el placebo mostraron niveles de 8-OHdG más elevados que los tejidos de los pacientes que consumieron el extracto de granada (Jarrard et al, 2021). Este estudio demuestra la importancia de controlar tanto el estrés oxidativo como su daño oxidante mediante el consumo de antioxidantes.…”
Section: -Hydroxy 2'-deoxyguanosine Expression In Cancerunclassified
See 1 more Smart Citation